Pre-emptive war under international law - Pietkiewicz, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The thesis is devoted to problems associated with the international legal regulation of pre-emptive war. It is quite obvious that this phenomenon has a logical context revealed in national security policies individual states pursue for themselves. In this regard, analysis was made of the prerequisites for the emergence of a new doctrine of pre-emptive war, and here analysis of the “Bush Doctrine” made it possible to reveal the characteristics of pre-emptive war. In addition, the article pays precise attention to the problem of correlation between the characteristics of pre-emptive war and preventive war. It has been separately established that the current stage of international legalization of pre-emptive war requires significant improvement in mechanisms preventing this phenomenon and the development of a system of sanctions. Important conclusions are drawn regarding the prospects for international consolidation and implementation of the pre-emptive war doctrine in the systems of international law.
Keywords: wojna zapobiegawcza; doktryna Busha; akt agresji; wojna; prawo międzynarodowe; Karta Narodów Zjednoczonych